Shaping the new economy versus space - Korenik, Stanisław (Kształtowanie się nowej gospodarki a przestrzeń, 2019)
The modern economy is characterised by turbulent, multi-directional transformations which are the result of the formation of the new economy. In the new economy, the role of the ICT sector is increasing and simultaneously the role of industry is declining. As part of the changes, the role of space is also changing. The new economy prefers spaces with multifunctional, modern structures that adapt to existing transformations
Biblioteka Regionalisty, 2019, Nr 19, s. 89-99
Keywords: Dolny Śląsk